Adverse effect of assisted reproductive technology-related hyperoestrogensim on the secretion and absorption of uterine fluid in superovulating mice during the peri-implantation period - Xia, Xinru; Zhang, Yuan; Cao, Meng; Yu, Xiang; Gao, Li; Qin, Lianju; Wu, Wei; Cui, Yugui; Liu, Jiayin (Frontiers in Endocrinology, 2023)
Objectives: This study aimed to investigate the potential mechanism of hyperoestrogensim elicited by ovulation induction affects endometrial receptivity and leads to embryo implantation abnormality or failure. Study design: Establishment of ovulation induction mouse model. Changes in mouse body weight, ovarian weight, serum E2 level and oestrous cycle were observed. During the peri-implantation period, morphological changes in the mouse uterus and implantation sites and the localization and protein levels of oestrogen receptors ERα and ERβ, the tight junction factors CLDN3 and OCLN, the aquaporins AQP3, AQP4 and AQP8, and the sodium channel proteins SCNN1α, SCNN1β and SCNN1γ were observed. The expression and cellular localization of ERα, CLDN3, AQP8 and SCNN1 β in RL95-2 cell line were also detected by western blotting and immunofluorescence. Results: Ovarian and body weights were significantly higher in the 5 IU and 10 IU groups than in the CON group. The E2 level was significantly higher in the 10 IU group than in the CON group. The mice in the 10 IU group had a disordered oestrous cycle and were in oestrus for a long time. At 5.5 dpc, significantly fewer implantation sites were observed in the 10 IU group than in the CON (p<0.001) and 5 IU (p<0.05) groups. The probability of abnormal implantation and abortion was higher in the 10 IU group than in the CON and 5 IU groups. CLDN3, OCLN, AQP8 and SCNN1β in the mouse endometrium were localized on the luminal epithelium and glandular epithelium and expression levels were lower in the 10 IU group than in the CON group. The protein expression level of ERα was increased by 50% in the 10 IU group compared to the CON group. The expressions of CLDN3, AQP8, SCNN1β in RL95-2 cell line were significantly depressed by the superphysiological E2, ERα agonist or ERβ agonist, which could be reversed by the oestrogen receptor antagonist. Conclusion: ART-induced hyperoestrogenism reduces CLDN3, AQP8 and SCNN1β expression through ERα, thereby destroying tight junctions and water and sodium channels in the endometrial cavity epithelium, which may cause abnormal implantation due to abnormal uterine fluid secretion and absorption.